Codeployment of a percutaneous edge‐to‐edge mitral valve repair device and a ventriculoseptal defect occluder device to address complex mitral regurgitation with leaflet perforation. Issue 6 (31st July 2020) - Addis, Dylan R.; Law, Mark; von Mering, Gregory; Ahmed, Mustafa
Abstract: An 80‐year‐old male with severe, complex mitral regurgitation (MR) after recent transcatheter aortic valve replacement presented in heart failure for percutaneous mitral valve repair and possible tricuspid valve repair. Transesopheageal echocardiography (TEE) demonstrated mixed Carpentier Types 1 and 2 components with annular dilation, two leaflet perforations, and excessive leaflet motion (P2 flail). There were three distinct MR jets appreciated reflecting a central coaptation defect and two posterior mitral valve leaflet perforations emanating from a cystic dilatation. Under TEE guidance transseptal puncture and percutaneous edge‐to‐edge mitral valve repair was performed with a MitraClip XTR device (Abbott, IL). A 10 mm Amplatzer Muscular VSD Occluder (Abbott, Abbott Park, IL) was deployed to close one of the perforations on the posterior leaflet with a significant reduction in MR severity. Attempts at crossing the remaining defect were unsuccessful and the procedure was concluded. The patient recovered uneventfully and transthoracic echocardiography on postoperative day (POD) 1 and again on POD 34 demonstrated normal systolic dominance on pulmonary venous Doppler interrogation, mild to moderate MR, and a mean transvalvular gradient of 5 mmHg. Both devices appeared firmly attached and stable. This is the first documented use of a VSD occluder device in this clinical scenario. Management of complex MR with an approach combining edge‐to‐edge repair for a central coaptation defect and leaflet flail with codeployment of a VSD occluder device to address a perforated leaflet is feasible and can achieve durable results.